Improved Cardiovascular and Cardiometabolic Risk in Patients With Type 1 Diabetes and Autoimmune Polyglandular Syndrome Switched From Glargine to Degludec Due to Hypoglycaemic Variability - Guarnotta, Valentina; Di Bella, Giulia; Pillitteri, Giuseppe; Ciresi, Alessandro; Giordano, Carla (Frontiers in Endocrinology, 2018)
Background: Cardiovascular disease is a frequent complication of type 1 diabetes (T1D). We evaluated the effectiveness of switching from glargine to degludec in reducing the cardiovascular risk factors, the Framingham risk score (FRS) and visceral adiposity index (VAI) in patients with T1D and autoimmune polyglandular syndrome (APS). Methods: We selected 66 T1D outpatients who had been on stable treatment with glargine for at least 5 years. Among them, 30 patients maintained glargine (group A), while 36 were switched to degludec (group B) for 12 months. At baseline and after 12 months of observation, clinical and metabolic parameters, insulin dose, 30-days blood glucose (BG) self monitoring, VAI and FRS were obtained. Results: At baseline, patients in group B had more hypoglycaemic episodes and prevalence of hypertension than those in group A. After 12 months on degludec, patients in group B had a significant decrease in BMI (p= 0.003), waist circumference (p< 0.001), total daily insulin as U/day and U/kg (p= 0.001 for both), basal insulin as U/day and U/kg (p= 0.001 for both), HbA1c (p< 0.001), mean (p= 0.035) and standard deviation of daily BG (p= 0.017), mean pre-meal BG (p= 0.016), number of hypoglycaemic episodes (p= 0.001), VAI (p= 0.012) and FRS (p= 0.019) and a significant increase in HDL-C (p< 0.001), compared to baseline. At 12 months of treatment a significant decrease in BMI (p= 0.017), WC (p= 0.003), SBP (p= 0.001), DBP (p= 0.005), basal insulin as U/day (p= 0.018) and U/kg (p= 0.045), HbA1c (p= 0.040) and FRS (p= 0.010) was observed in group B compared to group A. Conclusions: Our preliminary data suggest that 12 months’ treatment with degludec is associated with an improvement of glycaemic control, cardiometabolic and cardiovascular risk, compared to glargine, in patients with T1D and APS.